2012
DOI: 10.1002/jsfa.5829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garlic oil on milk fatty acid profile and lipogenesis‐related gene expression in mammary gland of dairy goats

Abstract: Garlic oil altered milk FA profile and these effects may not be related to the mammary lipogenesis-related genes expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
(125 reference statements)
2
10
0
Order By: Relevance
“…Information on the consequences of diet supplementation with garlic on product FA composition may help to confirm or disconfirm this trend, but relevant data are not well documented. Garlic oil did not change the FA composition of perirenal fat in bulls fed a maize silage diet [49], but increased PUFA and decreased C18:0 in milk FA in goats [50]. Despite these discrepancies between studies, it can be concluded that garlic oil holds enough promise, as a treatment to reduce the extent of lipolysis and/ or BH processes and thus increase PUFA and/or decrease C18:0, to warrant further research.…”
Section: Garlic Oilmentioning
confidence: 88%
“…Information on the consequences of diet supplementation with garlic on product FA composition may help to confirm or disconfirm this trend, but relevant data are not well documented. Garlic oil did not change the FA composition of perirenal fat in bulls fed a maize silage diet [49], but increased PUFA and decreased C18:0 in milk FA in goats [50]. Despite these discrepancies between studies, it can be concluded that garlic oil holds enough promise, as a treatment to reduce the extent of lipolysis and/ or BH processes and thus increase PUFA and/or decrease C18:0, to warrant further research.…”
Section: Garlic Oilmentioning
confidence: 88%
“…Goats were fed a basal diet without (control) or with GO infusion via ruminal fistula. The dose 0.04 g/kg BW was used in the present study according to the dose of GO in lamb research (0.01 g/kg BW) (Chaves et al, 2008) and our previous study in dairy goats (0.01, 0.02, and 0.03 g/kg BW) (Zhu et al, 2013). Accordingly, the dose was 0.8 g/d.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of a mixture of three of the most widespread terpenes in forage (α-pinene, limonene and β-caryophyllene) in the diet of lactating goats increased C18:3, c9,t11-CLA, and MUFA concentrations in their milk [ 107 ]. Other studies reported that the inclusion of garlic oil (0.57, 1.14, or 1.71 g/kg DM) in the diet of early lactating goats increased C18, c9,t11-CLA, t10,c12-CLA, MUFA, and PUFA in milk as garlic oil increased [ 105 ]. Finally, 10% Rosmarinus officinalis L. leaf supplementation increased the C18:2 and PUFA content in the milk of goats, while the same supplementation at a dose of 20% also increased C17:0 [ 103 ].…”
Section: Feeding Strategy To Improve the Fatty Acid Content In Shementioning
confidence: 99%